Bactericidal efficacy of two modified WHO-recommended alcohol-based hand rubs using two types of rub-in techniques for 15 s. (May 2021) - Suchomel, M.; Fritsch, F.; Kampf, G.
Summary: We evaluated the bactericidal efficacy of two modified WHO-recommended alcohol-based hand rubs (3 mL) after a 15-s rubbing period using two different rub-in techniques (three vs six steps). The formulation based on 80% w/w ethanol and 0.5% v/v glycerol (modified WHO I) showed a mean log10 -reduction of 3.63 ± 0.87 (six steps) and 3.80 ± 0.71 (three steps) which was inferior to the reference treatment (4.27 ± 0.98; six steps). The efficacy of the formulation based on 75% w/w isopropanol and 0.5% v/v glycerol (modified WHO II) was not inferior to the reference treatment for either rub-in technique.